PRIMARY ENGLISH TEACHERS PROFESSIONAL DEVELOPMENT DURING COVID19 PANDEMIC: A PRELIMINARY RESEARCH - Wiputra Cendana; Yonathan Winardi (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
There have been many ways offered as professional development (PD) for language teachers as well as conferences discussing its trends and alternatives. However, the world is facing CoVid19 pandemic that changes the context and media of English language teaching and learning in primary classrooms at present. Therefore, there is a need for novice teachers to be equipped by ways and opportunities in professional development that suit with the existing context and available media to apply PD. A preliminary cross-sectional survey was done in late July 2020 to get feedback on the ways primary English teachers of two private schools in West Jakarta did professional development. Possible solutions and opportunities are offered to assist them having a sustainable and meaningful professional development in the future during home-based learning (HBL) due to CoVid19 pandemic.The conclusion of the research is the primary English teachers have done various PD ways and need internal and external support from the school and local government mainly in the infrastructure, in order to provide the best possibility of the new learning experience with the students in the online classroom.